The Role of Indigenous Peoples in Forest Management Planning: A Comparative Analysis - Bauer, Maximilian; Schneider, Lukas; Huber, Anton (Journal of Selvicoltura Asean, 2024)
Indigenous peoples play a crucial role in forest management, possessing valuable traditional knowledge and practices that contribute to sustainable resource use. Despite their significance, the involvement of indigenous communities in formal forest management planning remains limited in many regions. Understanding their contributions is essential for developing effective and inclusive management strategies. This study aims to analyze the role of indigenous peoples in forest management planning through a comparative analysis of several case studies. The research seeks to identify best practices, challenges faced by indigenous communities, and the impact of their involvement on forest conservation and sustainability. A qualitative research approach was employed, utilizing case studies from different regions to gather insights into indigenous participation in forest management. Data were collected through interviews, focus group discussions, and document analysis. The analysis focused on comparing the effectiveness of indigenous-led management practices with conventional approaches. The findings indicate that indigenous peoples' involvement significantly enhances forest management outcomes. Case studies revealed that indigenous-led initiatives resulted in improved biodiversity conservation, sustainable resource management, and strengthened community resilience. Challenges such as land rights issues and lack of recognition by authorities were also identified. The research underscores the importance of integrating indigenous knowledge and practices into formal forest management planning. Recognizing and supporting the role of indigenous peoples can lead to more effective and sustainable forest management strategies, benefiting both ecosystems and local communities.